Bases metabólicas da rabdomiólise e atrofia muscular - Manda, Rodrigo Minoru [UNESP]; Moreto, Fernado [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 2010)
A gradual reduction in muscle mass began to occur physiologically after 30 years of age achieving clinical importance beyond the 5th decade of life. However it can occur earlier by the presence of food-energy deprivation and/or in association with trauma. Skeletal-muscle loss may occur by causes such as muscle denervation, disuse, nutritional deficiencies, hormonal imbalance and inflammation states. Muscle proteolysis occurs predominantly through ATP-ubiquitin-proteasomal pathway, cooperatively with systems of calpain and caspase 3. As proteolytic promoters there are the glucocorticoids, FOXO3 and the pro-inflammatory cytokines. TNFα activates NFκB either by increasing Ca++ intracellular as well by the increased reactive oxygen species. The over expression of genes MAFbx/atrogin 1 and MURF-1 are the main molecular markers of muscular atrophy whereas ubiquitin, calpain, TNFα and NFκB figure as the proteolytic markers. In general, oxidative stress is the main promoter of rhabdomyolysis and both mitochondrial disfunction and cellular apoptosis are the outcomes.

A redução da musculatura esquelética ou atrofia muscular ocorre gradativamente a partir dos 30 anos de idade, mas com significância importante a partir da 5ª década. Entretanto, ocorre em qualquer idade, na privação alimentar de carboidratos e no trauma. Pode ocorrer por denervação, desuso, deficiência nutricional, desequilíbrio hormonal e inflamação. A proteólise muscular ocorre predominantemente via ATP-ubiquitina-proteossoma e cooperativamente com os sistemas calpaína e caspase 3. Como promotores da proteólise figuram os glicocorticóides, o FOXO3 e as citocinas pró-inflamatórias. O TNFα, ativa o NF-κB tanto pelo Ca++ intracelular como pelas espécies reativas do oxigênio. Figuram como marcadores moleculares da atrofia muscular, a expressão aumentada dos genes MAFbx/atrogina 1 e MURF-1 e os marcadores proteolíticos como ubiquitina, calpaína, miostatina, TNFα e NF-κB. No geral, a rabdomiólise tem o estresse oxidativo como principal efetor e a disfunção mitocondrial, apoptose celular, como desfecho.
Metabolic basis of rhabdomyolysis and muscle atrophy
Keywords: Rhabdomyolysis; Proteolysis; Muscle atrophy; Cachexia; Rabdomiólise; Proteólise; Atrofia muscular; Caquexia